Persepsi Pengguna Terhadap Aplikasi Perpusda Wonosobo Di Dinas Kearsipan Dan Perpustakaan Daerah Kabupaten Wonosobo Dengan Pendekatan Pieces Framework - Anggraeni, Vira; Masruri, Anis (Jurnal Tadwin, 2022)
The purpose of this research is to determine the user's perceptions for the Wonosobo Library applications at the regional archives and libraries office of Wonosobo Regency with the PIECES framework approach. This research is included as descriptive quantitative research. The subjects in this research were active members of the Wonosobo Library application. The object of this research is the user's perception for the Wonosobo library application of the regional archives and libraries office of Wonosobo Regency. The sample obtained from the calculation with the Slovin formula are 100 respondents. Meanwhile, the sampling technique used is incidental sampling. This research has a single variable, namely the user's perception of Wonoosobo Library applications. This research instrument uses the PIECES framework, namely performance, information, economic, control, efficiency, and service. The scale used in this research is a Likert scale with 4 answer options. The data collection techniques in this study used 4 ways, namely questionnaires, observations, interviews, and documentations. The data analysis of this research used the mean and grand mean formulas. The results showed that the overall calculation of the sub-variables showed value of 3.07 which is on the scale range was included as a good category. The lowest sub-variable value is at 3.00 in the performance sub-variable which is included as a good category. The highest percentage of indicators shows the number 3.15 in the sub-variable economy (economic) which is included as a good category.